Between Past and Future - 1/14
Continuation of Prof. János Kis’ speech as a panelist in “Winners and Losers in the Great Transformations Since 1989” the third panel of the “Between Past and Future: The Revolutions of 1989 and the Struggle for Democracy in Central and Eastern Europe" international conference held at CEU in March 1999. The next person to deliver the speech after Prof. János Kis is Jeffrey Isaac, Professor at Indiana University. The final speech comes from Professor Vladimir Tismăneanu of Maryland University.